Asphalt concrete and preparation method thereof

By reacting polyether polyol with isocyanate in asphalt concrete to form polyurethane, combined with glass fiber, nanosilicon dioxide and montmorillonite, a cross-linked network structure is formed, which solves the problems of asphalt concrete road wear and deformation and improves resistance Ruts and durability extend service life.

CN116332567BActive Publication Date: 2025-01-14NANJING SUJIA CONSTR ENG CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310209684.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-07
Publication Date
2025-01-14
Estimated Expiration
2043-03-07

AI Technical Summary

Technical Problem

Asphalt concrete pavement is prone to wear, depression and deformation in the speed reduction or slowing areas such as highway import and exit, payment stations, etc. due to the increase in traffic volume and vehicle load, resulting in ruts and affecting the flatness and service life of the road surface.

Method used

Using an asphalt concrete formula, including asphalt, coarse aggregate, fine aggregate, glass fiber, rubber powder, polyether polyol, isocyanate, chain extender, nano silica and montmorillonite, through polyether polyol and The isocyanate reaction forms polyurethane, forming a crosslinking network structure, combining glass fibers, nanosilicon dioxide and montmorillonite, enhancing the strength, deformation resistance and durability of asphalt concrete.

Benefits of technology

It significantly improves the rut resistance, high temperature resistance and service life of asphalt concrete, reduces the recess and permanent deformation of the pavement, and extends the fatigue life of the asphalt concrete pavement.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004112172820000051
    Figure BDA0004112172820000051
  • Figure BDA0004112172820000091
    Figure BDA0004112172820000091
Patent Text Reader

Abstract

The present application relates to the field of concrete materials, and specifically discloses an asphalt concrete and a preparation method thereof. An asphalt concrete comprises the following raw materials in parts by weight: 10-25 parts of asphalt, 50-70 parts of coarse aggregate, 10-20 parts of fine aggregate, 5-10 parts of glass fiber, 3-5 parts of rubber powder, 10-20 parts of polyether polyol, 10-20 parts of isocyanate, 3-5 parts of chain extender, 1-3 parts of nano-silicon dioxide, and 3-5 parts of montmorillonite. An asphalt concrete has excellent resilience, strength and anti-rutting performance, and is polymerized in an asphalt concrete system to generate a polyether polyurethane, which can be combined with asphalt to form a multi-dimensional cross-linked network structure, improve the bonding force between the components in the asphalt concrete system, promote the asphalt concrete to have excellent shear stress, strength and wear resistance, and reduce the rutting phenomenon of asphalt concrete pavement under traffic load.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of concrete materials, and more specifically, to an asphalt concrete and a preparation method thereof. Background Art

[0002] Asphalt concrete refers to a mixture made by artificially selecting mineral materials with a certain graded composition and a certain proportion of road asphalt materials under strict process conditions.

[0003] However, in recent years, people have found in real life that in deceleration or slow-moving areas such as entrances and exits of highways and intersections of toll stations, due to the increase in traffic volume and the long time of vehicle load on the road surface, the wear, depression and deformation of the asphalt concrete pavement are more obvious, thus forming rutting on the asphalt concrete pavement, affecting the flatness of the asphalt concrete pavement, shortening the service life of the asphalt concrete pavement, and reducing driving safety. Summary of the invention

[0004] In order to improve the rutting phenomenon of asphalt concrete pavement and enhance the durability of asphalt concrete pavement, the present application provides an asphalt concrete and a preparation method thereof.

[0005] In the first aspect, the present application provides an asphalt concrete, which adopts the following technical solution:

[0006] An asphalt concrete comprises the following raw materials in parts by weight: 10-25 parts of asphalt, 50-70 parts of coarse aggregate, 10-20 parts of fine aggregate, 5-10 parts of glass fiber, 3-5 parts of rubber powder, 10-20 parts of polyether polyol, 10-20 parts of isocyanate, 3-5 parts of chain extender, 1-3 parts of nano silicon dioxide and 3-5 parts of montmorillonite.

[0007] By adopting the above technical scheme, polyether polyol and isocyanate generate polyether polyurethane under the action of chain extender, which has the advantages of high elasticity, high and low temperature resistance and high stability, replacing the phenomenon of easy hydrolysis of traditional polyester polyurethane. Aromatic compounds in asphalt react with polyether polyurethane to form a cross-linked network structure in the asphalt concrete system, thereby improving the strength and deformation resistance of asphalt concrete, and promoting asphalt concrete to have certain elastic recovery performance, thereby promoting asphalt concrete to have high temperature resistance and anti-rutting performance. Glass fiber can improve the strength, crack resistance, wear resistance and load capacity of asphalt concrete, reduce the phenomenon of dents, cracks and wear of asphalt concrete, and can also absorb a certain amount of heat and conduct it to the polyurethane network structure, promoting elastic recovery, and further reducing the rutting phenomenon of asphalt concrete.

[0008] Rubber powder can be added into the pores between coarse aggregate and fine aggregate, improving the adhesion of the components in the asphalt concrete system, reducing the phenomenon of asphalt concrete fracture, improving the density, strength and impermeability of the asphalt concrete system, reducing the permanent deformation of asphalt concrete pavement due to insufficient strength under the action of traffic loads, and producing rutting, thereby improving the durability of asphalt concrete.

[0009] When nano-silicon dioxide is added to the asphalt concrete system, it can combine with the unsaturated double bonds in the asphalt to generate a stable three-dimensional network structure. In the process of combining polyurethane and asphalt, the nano-silicon dioxide can fill the gaps between the polyurethane molecules through its own healing effect, thereby enhancing the bonding force between the polyurethane and the asphalt, thereby improving the density, shear stress and strength of the asphalt concrete. Nano-silicon dioxide is small in size, and the interfacial bonding strength between the asphalt and the nano-silicon dioxide is large. Therefore, the addition of nano-silicon dioxide makes the network structure in the asphalt concrete system more compact and stable, further extending the fatigue life and anti-rutting performance of the asphalt pavement. On the other hand, nano-silicon dioxide has a strong shielding effect on ultraviolet rays, so it can improve the aging resistance of asphalt concrete and further extend the service life of asphalt concrete.

[0010] Montmorillonite can be evenly distributed in the asphalt concrete system, interspersed between polyurethane and asphalt macromolecules, improving the heat resistance and stiffness of asphalt concrete, and at the same time significantly improving the rutting phenomenon of asphalt concrete pavement.

[0011] Preferably, the asphalt concrete raw material also includes 0.5-1 part of starch sodium crystals.

[0012] By adopting the above technical solution, starch nanocrystals can be tightly combined with the asphalt matrix and polyurethane macromolecular chains to produce hydrogen bonding, thereby improving the strength, toughness and shear stress of asphalt concrete, increasing the load capacity of asphalt concrete, and reducing the effect of traffic load on the road surface for a long time, causing the phenomenon of depression and permanent deformation of asphalt concrete pavement.

[0013] On the other hand, the hydroxyl groups in the starch nanocrystal molecules can form hydrogen bonds with the silicon hydroxyl groups on the surface of the glass fibers. At the same time, the starch nanocrystals can also interact with polyurethane to improve the strength and toughness of the polyurethane matrix. Thus, the starch nanocrystals can improve the bonding force between the glass fibers and the polyurethane, forming a network structure in the asphalt concrete, and enabling the asphalt concrete to have stable strength, toughness and shear stress.

[0014] Preferably, the asphalt concrete raw material also includes 5-10 parts of hexadecyltrimethylammonium bromide.

[0015] By adopting the above technical scheme, hexadecyl trimethyl ammonium bromide enters the molecular interlayer of montmorillonite through ion exchange reaction to form montmorillonite with a larger interlayer spacing, thereby promoting the polymerization of polyether polyol and isocyanate between the interlayer spacing of montmorillonite to form polyurethane, promoting the uniform dispersion of montmorillonite in the polyurethane and asphalt concrete system, and reducing the agglomeration of montmorillonite particles. The organic modification of montmorillonite by hexadecyl trimethyl ammonium bromide promotes montmorillonite to effectively block and inhibit the decomposition of polyurethane molecular chains and the volatilization of decomposition products, improve the thermal oxygen stability of polyurethane and montmorillonite composite materials, further improve the heat resistance of asphalt concrete, reduce the deformation and rutting phenomenon of asphalt concrete pavement at high temperature, thereby improving the deformation resistance and rutting resistance of asphalt concrete.

[0016] Preferably, the asphalt concrete raw material also includes 0.5-1.5 parts of acrylamide, 0.5-1.5 parts of acrylic acid and 0.5-1 part of initiator.

[0017] By adopting the above technical solution, acrylamide and acrylic acid are polymerized in asphalt concrete, and the carbonyl group of polyacrylic acid and the carbonyl group of polyacrylamide, nitrogen-hydrogen bonds and double bonds of rubber powder are grafted to form a cross-linked network structure with rubber powder as nodes, thereby improving the stability of aggregate and asphalt in the asphalt concrete system, improving the density of asphalt concrete, and promoting asphalt concrete to have certain anti-seepage performance, thereby reducing the phenomenon of cracking and stratification of asphalt concrete pavement due to rain erosion, thereby improving the durability of asphalt concrete. At the same time, the modification of acrylic acid and acrylamide on rubber powder promotes the rubber powder to be evenly dispersed in asphalt concrete, and the hydrogen bonding force between acrylic acid, asphalt and polyurethane forms a stable multi-dimensional network structure in the asphalt concrete system, promoting asphalt concrete to have certain anti-deformation performance, reducing the phenomenon of deformation and denting of asphalt concrete pavement, and further improving the durability of asphalt concrete.

[0018] Preferably, the chain extender is at least one of triethanolamine and diethanolamine.

[0019] By adopting the above technical solution, triethanolamine and diethanolamine are used as chain extenders for the reaction of polyether polyol and isocyanate, which can adjust the reaction speed of the reaction system and increase the viscosity of the product polyurethane. At the same time, triethanolamine and diethanolamine are adsorbed on the surface of asphalt to form hydrogen bonds, which promotes the uniform dispersion of asphalt in asphalt concrete slurry, improves the dispersibility of asphalt concrete system, reduces asphalt deposition, thereby reducing the stratification phenomenon of asphalt concrete and further improves the durability of asphalt concrete.

[0020] Preferably, the coarse aggregate is crushed stone with a grade of 10-20 mm.

[0021] Preferably, the fine aggregate is quartz particles with a grade of 2-5 mm.

[0022] By adopting the above technical scheme and selecting appropriate asphalt aggregate grading, the aggregate porosity of asphalt concrete can be reduced, the asphalt concrete can have a suitable density, the coarse aggregate and fine aggregate can be interlocked with each other, the compaction stability of the asphalt concrete system can be improved, and the occurrence of rutting on asphalt pavement can be further reduced.

[0023] In a second aspect, the present application provides a method for preparing asphalt concrete, which adopts the following technical solution:

[0024] A method for preparing asphalt concrete comprises the following specific steps:

[0025] S1: Dehydrating the polyether polyol, mixing it with isocyanate and chain extender, and heating to react to form polyurethane, and then mixing nano-silica with polyurethane to form a polyurethane-nano-silica mixture;

[0026] S2: Heat and melt the asphalt, then mix it with coarse aggregate, fine aggregate and glass fiber, heat it to 180-200°C to form a mixture, then cool the mixture to 110-120°C, finally add rubber powder, montmorillonite and polyurethane-nano silica mixture to the mixture and mix and stir to obtain asphalt concrete.

[0027] By adopting the above technical solution, the prepared asphalt concrete has excellent strength, deformation resistance and elastic recovery performance, thereby reducing the permanent deformation and depression of the asphalt concrete pavement caused by insufficient strength and long-term traffic load, and reducing the rutting phenomenon of the road surface.

[0028] Preferably, starch nanocrystals are dissolved in an ethanol solution to form a starch nanocrystal solution, and then glass fibers are added to the starch nanocrystal solution and mixed, and then the glass fibers are taken out, dried, and heated to obtain modified glass fibers, and then the modified glass fibers are added to the mixture and mixed with rubber powder, montmorillonite and a polyurethane-nanosilica mixture to obtain asphalt concrete.

[0029] By adopting the above technical scheme, starch nanocrystals are grafted with glass fibers, so that starch nanocrystals can enhance the interfacial strength between glass fibers and macromolecules such as polyurethane and asphalt, thereby enhancing the binding force of each molecule in the asphalt concrete system, increasing the density, and further reducing the rutting phenomenon on the asphalt concrete pavement.

[0030] In summary, this application has the following beneficial effects:

[0031] 1. Since the present application adopts polyether polyol and isocyanate to react to generate polyurethane, polyurethane is compounded with asphalt, which makes asphalt concrete have certain resilience, high temperature resistance and deformation resistance, thereby improving the anti-rutting performance of asphalt concrete. Glass fiber is used to improve the strength and flexibility of asphalt concrete, while nano-silica, rubber powder and montmorillonite can be compounded and filled into the voids of asphalt concrete to form a cross-linked network structure in asphalt concrete, improve the binding force of each component in the asphalt concrete system, improve the compactness, shear stress and strength of asphalt concrete, and reduce deformation and rutting under traffic load.

[0032] 2. In this application, starch nanocrystals are preferably used to form hydrogen bonding forces with asphalt and polyurethane matrices. At the same time, the surface of glass fibers can be modified to enhance the binding force of the components in the asphalt concrete system, improve the degree of cross-linking of the components in the asphalt concrete system, and enable the asphalt concrete to have higher strength, shear stress and deformation resistance, thereby reducing the occurrence of cracking, dents and rutting on the asphalt concrete pavement. DETAILED DESCRIPTION

[0033] The present application is further described in detail below with reference to the embodiments.

[0034] In this specific embodiment, without other special circumstances, the components used are as follows:

[0035] The asphalt selected is Shell Asphalt Co., Ltd. 70# asphalt.

[0036] The glass fiber has a diameter of 12 μm-13 μm and a length of 6 mm.

[0037] The polyether polyol selected is polyether diol 4000.

[0038] The isocyanate selected is isophorone diisocyanate.

[0039] The particle size of rubber powder is 80 mesh.

[0040] The particle size of montmorillonite is 0.2μm-0.3μm.

[0041] The particle size of nano-silicon dioxide is 20nm-30nm.

[0042] Example

[0043] Example 1

[0044] An asphalt concrete comprises the following raw materials in parts by weight: 20 kg of asphalt, 60 kg of coarse aggregate, 15 kg of fine aggregate, 8 kg of glass fiber, 4 kg of rubber powder, 15 kg of polyether polyol, 15 kg of isocyanate, 4 kg of chain extender, 2 kg of nano silicon dioxide, and 4 kg of montmorillonite. The particle size of the coarse aggregate is 15 mm, the particle size of the fine aggregate is 3 mm, and the chain extender is a mixture of triethanolamine and diethanolamine in a mass ratio of 1:1.

[0045] A method for preparing asphalt concrete comprises the following specific steps:

[0046] S1: Dehydrate the polyether polyol at 110°C for 1.5 hours, then mix it with isocyanate and chain extender, stir it at 200 r / min for 5 minutes, heat it to 90°C for reaction for 1 hour to form polyurethane, then mix nano-silica with polyurethane, stir it at 200 r / min for 20 minutes, continue to keep warm and react for 1 hour to form a polyurethane-nano-silica mixture.

[0047] S2: Heat the asphalt to 130°C to melt, stir at 1000r / min for 20min, then mix with coarse aggregate, fine aggregate and glass fiber, heat to 180°C, stir at 800r / min for 20min to form a mixture, then cool the mixture to 110°C, finally add rubber powder, montmorillonite and polyurethane-nanosilica mixture to the mixture, mix and stir at 500r / min for 30min to obtain asphalt concrete.

[0048] Example 2-3

[0049] The difference between Example 2-3 and Example 1 is that the contents of the components in Examples 1-3 are different, as shown in Table 1.

[0050] Table 1: Content of each component in Examples 1-3

[0051]

[0052] Example 4

[0053] The difference between Example 4 and Example 1 is that the chain extender in the asphalt concrete raw material is triethanolamine, the particle size of the coarse aggregate is 10 mm, and the particle size of the fine aggregate is 5 mm.

[0054] Example 5

[0055] The difference between Example 5 and Example 1 is that the chain extender in the asphalt concrete raw material is diethanolamine, the particle size of the coarse aggregate is 20 mm, and the particle size of the fine aggregate is 2 mm.

[0056] Example 6

[0057] The difference between Example 6 and Example 1 is that the asphalt concrete raw material also includes 0.8 kg of starch nanocrystals.

[0058] A method for preparing asphalt concrete comprises the following specific steps:

[0059] S1: Dissolve starch nanocrystals in 70% ethanol aqueous solution, the mass ratio of ethanol aqueous solution to starch nanocrystals is 20:1, and ultrasonically disperse for 1 hour to form a starch nanocrystal solution. Add glass fiber to the starch nanocrystal solution and soak it for reaction for 24 hours. Take out the reacted glass fiber, wash it with ethanol, and then dry it at 180°C for 3 hours to obtain modified glass fiber.

[0060] S2: Dehydrate the polyether polyol at 110°C for 1.5 hours, then mix it with isocyanate and chain extender, stir it at 200 r / min for 5 minutes, heat it to 90°C for reaction for 1 hour to form polyurethane, then mix nano-silica with polyurethane, stir it at 200 r / min for 20 minutes, continue to keep warm and react for 1 hour to form a polyurethane-nano-silica mixture.

[0061] S3: Heat the asphalt to 130°C to melt, stir at 1000r / min for 20min, then mix with coarse aggregate, fine aggregate and modified glass fiber, heat to 180°C, stir at 800r / min for 20min to form a mixture, then cool the mixture to 110°C, finally add rubber powder, montmorillonite and polyurethane-nanosilica mixture to the mixture, stir at 500r / min for 30min to obtain asphalt concrete.

[0062] Example 7

[0063] The difference between Example 7 and Example 6 is that the amount of starch nanocrystals used in the asphalt concrete is 0.5 kg.

[0064] Example 8

[0065] The difference between Example 8 and Example 6 is that the amount of starch nanocrystals used in the asphalt concrete is 1 kg.

[0066] Example 9

[0067] The difference between Example 9 and Example 6 is that the asphalt concrete raw material also includes 8 kg of hexadecyltrimethylammonium bromide.

[0068] A method for preparing asphalt concrete comprises the following specific steps:

[0069] S1: Dissolve starch nanocrystals in 70% ethanol aqueous solution, the mass ratio of ethanol aqueous solution to starch nanocrystals is 20:1, and ultrasonically disperse for 1 hour to form a starch nanocrystal solution. Add glass fiber to the starch nanocrystal solution and soak it for reaction for 24 hours. Take out the reacted glass fiber, wash it with ethanol, and then dry it at 180°C for 3 hours to obtain modified glass fiber.

[0070] S2: Mix montmorillonite with deionized water in a mass ratio of 500:1, stir at 2000 r / min for 10 min at 80°C to form a montmorillonite suspension, then use hydrochloric acid and sodium hydroxide to adjust the pH value of the montmorillonite suspension to 5, then mix hexadecyltrimethylammonium bromide with deionized water in a mass ratio of 6:1, stir at 300 r / min for 10 min at 30°C to form a hexadecyltrimethylammonium bromide mixed solution, then mix the hexadecyltrimethylammonium bromide mixed solution with the montmorillonite suspension, stir at 2000 r / min for 2 h at 80°C, vacuum filter, wash with deionized water, dry to constant mass at 100°C, grind, and obtain modified montmorillonite.

[0071] S3: Dehydrate the polyether polyol at 110°C for 1.5 hours, then mix it with isocyanate and chain extender, stir it at 200 r / min for 5 minutes, heat it to 90°C for reaction for 1 hour to form polyurethane, then mix nano-silica, modified montmorillonite and polyurethane, stir it at 200 r / min for 20 minutes, continue to keep warm and react for 1 hour to form a modified polyurethane composite.

[0072] S4: Heat the asphalt to 130°C to melt, stir at 1000r / min for 20min, then mix with coarse aggregate, fine aggregate and modified glass fiber, heat to 180°C, stir at 800r / min for 20min to form a mixture, then cool the mixture to 110°C, finally add rubber powder and modified polyurethane compound to the mixture, stir at 500r / min for 30min to obtain asphalt concrete.

[0073] Example 10

[0074] The difference between Example 10 and Example 9 is that the amount of hexadecyltrimethylammonium bromide used in the asphalt concrete is 5 kg.

[0075] Embodiment 11

[0076] The difference between Example 11 and Example 9 is that the amount of hexadecyltrimethylammonium bromide used in the asphalt concrete is 10 kg.

[0077] Example 12

[0078] The difference between Example 12 and Example 9 is that the asphalt concrete raw materials also include 1 kg of acrylamide, 1 kg of acrylic acid, and 0.8 kg of initiator, wherein the initiator is potassium persulfate.

[0079] A method for preparing asphalt concrete comprises the following specific steps:

[0080] S1: Dissolve starch nanocrystals in 70% ethanol aqueous solution, the mass ratio of ethanol aqueous solution to starch nanocrystals is 20:1, and ultrasonically disperse for 1 hour to form a starch nanocrystal solution. Add glass fiber to the starch nanocrystal solution and soak it for reaction for 24 hours. Take out the reacted glass fiber, wash it with ethanol, and then dry it at 180°C for 3 hours to obtain modified glass fiber.

[0081] S2: The rubber powder was washed with acetone at 50°C for 1 hour, and then filtered with suction until the filtrate was colorless. The rubber powder was then dried at 80°C for 4 hours to obtain pretreated rubber powder. The pretreated rubber powder, acrylic acid, acrylamide and initiator were mixed, stirred at 800 r / min for 10 minutes, heated to 60°C in a water bath under the protection of nitrogen, and stirred at 500 r / min for 3.5 hours. The mixture was washed with distilled water and dried at 80°C to obtain modified rubber powder.

[0082] S3: Mix montmorillonite with deionized water in a mass ratio of 500:1, stir at 2000 r / min for 10 min at 80°C to form a montmorillonite suspension, then use hydrochloric acid and sodium hydroxide to adjust the pH value of the montmorillonite suspension to 5, then mix hexadecyltrimethylammonium bromide with deionized water in a mass ratio of 6:1, stir at 300 r / min for 10 min at 30°C to form a hexadecyltrimethylammonium bromide mixed solution, then mix the hexadecyltrimethylammonium bromide mixed solution with the montmorillonite suspension, stir at 2000 r / min for 2 h at 80°C, vacuum filter, wash with deionized water, dry to constant mass at 100°C, grind, and obtain modified montmorillonite.

[0083] S4: Dehydrate the polyether polyol at 110°C for 1.5 hours, then mix it with isocyanate and chain extender, stir it at 200 r / min for 5 minutes, heat it to 90°C for reaction for 1 hour to form polyurethane, then mix nano-silica, modified montmorillonite and polyurethane, stir it at 200 r / min for 20 minutes, continue to keep warm and react for 1 hour to form a modified polyurethane composite.

[0084] S5: Heat the asphalt to 130°C to melt, stir at 1000r / min for 20min, then mix with coarse aggregate, fine aggregate and modified glass fiber, heat to 180°C, stir at 800r / min for 20min to form a mixture, then cool the mixture to 110°C, finally add modified rubber powder and modified polyurethane compound to the mixture and stir at 500r / min for 30min to obtain asphalt concrete.

[0085] Example 13

[0086] The difference between Example 13 and Example 12 is that the amount of acrylamide used in the asphalt concrete raw material is 0.5 kg, the amount of acrylic acid used is 1.5 kg, and the amount of initiator used is 0.5 kg.

[0087] Embodiment 14

[0088] The difference between Example 14 and Example 12 is that the amount of acrylamide used in the asphalt concrete raw material is 1.5 kg, the amount of acrylic acid used is 0.5 kg, and the amount of initiator used is 1 kg.

[0089] Comparative Example

[0090] Comparative Example 1

[0091] The difference between Comparative Example 1 and Example 1 is that no glass fiber is used in the asphalt concrete raw material.

[0092] Comparative Example 2

[0093] The difference between Comparative Example 2 and Example 1 is that no glass fiber and nano-silicon dioxide are used in the asphalt concrete raw materials.

[0094] Comparative Example 3

[0095] The difference between Comparative Example 3 and Example 1 is that no glass fiber, nano-silicon dioxide and rubber powder are used in the asphalt concrete raw materials.

[0096] Performance testing

[0097] The asphalt concrete provided in Examples 1-14 and Comparative Examples 1-3 of the present application was subjected to the following performance tests, and the specific test results are shown in Table 2.

[0098] Detection Methods

[0099] 1. Marshall stability

[0100] Refer to the "T0709-2011 Marshall Stability Test for Asphalt Mixtures" in the standard JTGE20-2011 "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering" to test the high temperature resistance of asphalt concrete.

[0101] 2. Needle Penetration

[0102] Refer to T0604-2011 "Asphalt Penetration Test" in the standard JTGE20-2011 "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering" to test the strength and shear failure resistance of asphalt concrete.

[0103] 3. Anti-rutting performance

[0104] The test was carried out with reference to the "T0719-2011 Asphalt Mixture Rutting Test" in JTG-E20-2011 "Highway Engineering Asphalt and Asphalt Mixture Test Procedures". The test was carried out at 60°C and a wheel pressure of 0.7MPa. The asphalt concrete was made into a plate sample with a size of 300mm×300mm. The test wheel walked back and forth on the plate sample at a rolling speed of 42 times / min to measure the rutting stability.

[0105] Table 2: Performance test data table

[0106]

[0107] It can be seen from the performance test data table of Examples 1-5 that the asphalt concrete prepared in this application has excellent strength, high temperature resistance and rutting resistance. With the mutual cooperation of various components, a multi-dimensional network structure is formed in the asphalt concrete system, thereby increasing the shear stress of the asphalt concrete, reducing the deformation, wear and depression of the asphalt concrete pavement under the action of traffic load, and further improving the rutting resistance of the asphalt concrete. At the same time, polyether polyols and isocyanates react in the asphalt concrete system to generate polyether polyurethane, and the polyether polyurethane undergoes a cross-linking reaction, thereby causing the asphalt concrete to have excellent high elasticity, high temperature resistance and deformation resistance. In Examples 1-5, the content of each component in the asphalt concrete raw material is different. From the performance test results, it can be seen that the asphalt concrete prepared in Example 1 has the best performance.

[0108] In Examples 6-8, different amounts of starch nanocrystals were added to asphalt concrete. From the performance test results, it can be seen that the strength and rutting resistance of the asphalt concrete are improved, which further illustrates that the starch nanocrystals form a cross-linked network in the asphalt concrete system by combining with asphalt and polyurethane macromolecules. At the same time, the starch nanocrystals can also form hydrogen bonds with the silanol groups on the surface of the glass fiber, thereby improving the bonding force between the glass fiber and the polyurethane and asphalt, further improving the strength, toughness and shear stress of the asphalt concrete system, and reducing the phenomenon of fracture and depression of the asphalt concrete pavement under traffic loads.

[0109] In Examples 9-11, different amounts of cetyltrimethylammonium bromide were added to the asphalt concrete system. From the test results, it can be seen that the comprehensive performance of the asphalt concrete is improved, which further illustrates the organic modification of montmorillonite by cetyltrimethylammonium bromide, which promotes the uniform dispersion of montmorillonite in the asphalt and polyurethane matrix, improves the thermal oxidation stability of the composite product of polyurethane and montmorillonite, reduces deformation and rutting of asphalt concrete pavement under high temperature, and improves the deformation resistance and rutting resistance of asphalt concrete.

[0110] In Examples 12-14, acrylamide and acrylic acid are added to the asphalt concrete system to undergo polymerization in the asphalt concrete to modify the rubber powder. Performance test results show that the rutting resistance and strength of the asphalt concrete are improved. Acrylamide and acrylic acid polymerize to form hydrogen bonds with asphalt, polyurethane and rubber powder to form a multi-dimensional cross-linked network structure, thereby increasing the bonding force between the components in the asphalt concrete, increasing the density and strength of the asphalt concrete, thereby reducing cracking and stratification of the asphalt concrete, and further improving the rutting resistance of the asphalt concrete.

[0111] By comparing the performance test results of comparative example 1 and embodiment 1, it can be seen that the heat resistance and strength of asphalt concrete are reduced without using glass fiber in comparative example 1, and the anti-rutting performance of asphalt concrete is also affected to a certain extent. This further illustrates that glass fiber plays an important role in improving the comprehensive performance of asphalt concrete, such as heat resistance, wear resistance and strength.

[0112] By comparing the performance test results of Comparative Example 2 with those of Example 1, it can be seen that the comprehensive performance of asphalt concrete in Comparative Example 1 is significantly reduced without the use of glass fiber and nano-silicon dioxide. On the one hand, it illustrates the promoting effect of nano-silicon dioxide on the strength, shear stress and anti-rutting performance of asphalt concrete. On the other hand, the significant decline in the performance of asphalt concrete prepared in Comparative Example 2 further illustrates the synergistic effect of nano-silicon dioxide and glass fiber, which can further improve the strength and anti-rutting performance of asphalt concrete.

[0113] Through the performance test results of Comparative Example 3 and Example 1, it can be seen that Comparative Example 3 does not use glass fiber, nano-silica and rubber powder, and the comprehensive performance of asphalt concrete is greatly reduced, which shows that the rubber powder promotes the density, strength and anti-rutting performance of asphalt concrete. On the other hand, it further illustrates that glass fiber, nano-silica and rubber powder are combined with each other in the asphalt and polyurethane matrix to form a multi-dimensional cross-linked network structure, which better toughens and strengthens the asphalt concrete and reduces the rutting phenomenon of the asphalt concrete pavement under the action of traffic load.

[0114] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. An asphalt concrete, characterized in that: The invention comprises the following raw materials in parts by weight: 10-25 parts of asphalt, 50-70 parts of coarse aggregate, 10-20 parts of fine aggregate, 5-10 parts of glass fiber, 3-5 parts of rubber powder, 10-20 parts of polyether polyol, 10-20 parts of isocyanate, 3-5 parts of chain extender, 1-3 parts of nano silicon dioxide, 3-5 parts of montmorillonite, 0.5-1 parts of starch nanocrystals, and 5-10 parts of hexadecyltrimethylammonium bromide; The preparation method of asphalt concrete comprises the following specific steps: S1: Dissolve starch nanocrystals in 70% ethanol aqueous solution, the mass ratio of ethanol aqueous solution to starch nanocrystals is 20:1, and disperse by ultrasonic for 1 hour to form a starch nanocrystal solution. Add glass fiber to the starch nanocrystal solution and soak for reaction for 24 hours. Take out the reacted glass fiber, wash it with ethanol, and then dry it at 180°C for 3 hours to obtain modified glass fiber. S2: Mix montmorillonite with deionized water, the mass ratio of deionized water to montmorillonite is 500:1, stir at 2000 r / min for 10 min at 80°C to form a montmorillonite suspension, then use hydrochloric acid and sodium hydroxide to adjust the pH value of the montmorillonite suspension to 5, then mix hexadecyltrimethylammonium bromide with deionized water, the mass ratio of deionized water to hexadecyltrimethylammonium bromide is 6:1, stir at 30°C at 300 r / min for 10 min to form a hexadecyltrimethylammonium bromide mixed solution, then mix the hexadecyltrimethylammonium bromide mixed solution with the montmorillonite suspension, stir at 80°C at 2000 r / min for 2 h, vacuum filter, wash with deionized water, dry to constant mass at 100°C, grind, and obtain modified montmorillonite; S3: Dehydrate the polyether polyol at 110°C for 1.5 hours, then mix it with isocyanate and chain extender, stir it at 200 r / min for 5 minutes, heat it to 90°C for reaction for 1 hour to form polyurethane, then mix nano-silica, modified montmorillonite and polyurethane, stir it at 200 r / min for 20 minutes, continue to keep warm for reaction for 1 hour to form modified polyurethane composite; S4: Heat the asphalt to 130℃ to melt, stir at 1000r / min for 20min, then mix with coarse aggregate, fine aggregate and modified glass fiber, heat to 180℃, stir at 800r / min for 20min to form a mixture, then cool the mixture to 110℃, finally add rubber powder and modified polyurethane compound to the mixture, mix and stir at 500r / min for 30min to obtain asphalt concrete.

2. An asphalt concrete, characterized in that: The invention comprises the following raw materials in parts by weight: 10-25 parts of asphalt, 50-70 parts of coarse aggregate, 10-20 parts of fine aggregate, 5-10 parts of glass fiber, 3-5 parts of rubber powder, 10-20 parts of polyether polyol, 10-20 parts of isocyanate, 3-5 parts of chain extender, 1-3 parts of nano silicon dioxide, 3-5 parts of montmorillonite, 0.5-1 parts of starch nanocrystals, 5-10 parts of hexadecyltrimethylammonium bromide, 0.5-1.5 parts of acrylamide, 0.5-1.5 parts of acrylic acid and 0.5-1 parts of initiator; The preparation method of asphalt concrete comprises the following specific steps: S1: Dissolve starch nanocrystals in 70% ethanol aqueous solution, the mass ratio of ethanol aqueous solution to starch nanocrystals is 20:1, and disperse by ultrasonic for 1 hour to form a starch nanocrystal solution. Add glass fiber to the starch nanocrystal solution and soak for reaction for 24 hours. Take out the reacted glass fiber, wash it with ethanol, and then dry it at 180°C for 3 hours to obtain modified glass fiber. S2: The rubber powder is washed with acetone at 50°C for 1 hour, and then filtered with washing suction until the filtrate is colorless, and then the rubber powder is dried at 80°C for 4 hours to obtain pretreated rubber powder, and then the pretreated rubber powder, acrylic acid, acrylamide and initiator are mixed, stirred at a speed of 800r / min for 10 minutes, heated to 60°C in a water bath under the protection of nitrogen, stirred at a speed of 500r / min for 3.5 hours, washed with distilled water, and dried at 80°C to obtain modified rubber powder; S3: Mix montmorillonite with deionized water, the mass ratio of deionized water to montmorillonite is 500:1, stir at 2000 r / min for 10 min at 80°C to form a montmorillonite suspension, then use hydrochloric acid and sodium hydroxide to adjust the pH value of the montmorillonite suspension to 5, then mix hexadecyltrimethylammonium bromide with deionized water, the mass ratio of deionized water to hexadecyltrimethylammonium bromide is 6:1, stir at 30°C at 300 r / min for 10 min to form a hexadecyltrimethylammonium bromide mixed solution, then mix the hexadecyltrimethylammonium bromide mixed solution with the montmorillonite suspension, stir at 80°C at 2000 r / min for 2 h, vacuum filter, wash with deionized water, dry to constant mass at 100°C, grind, and obtain modified montmorillonite; S4: Dehydrate the polyether polyol at 110°C for 1.5 hours, then mix with isocyanate and chain extender, stir at 200 r / min for 5 minutes, heat to 90°C for reaction for 1 hour to form polyurethane, then mix nano-silica, modified montmorillonite and polyurethane, stir at 200 r / min for 20 minutes, continue to keep warm for reaction for 1 hour to form modified polyurethane composite; S5: Heat the asphalt to 130℃ to melt, stir at 1000r / min for 20min, then mix with coarse aggregate, fine aggregate and modified glass fiber, heat to 180℃, stir at 800r / min for 20min to form a mixture, then cool the mixture to 110℃, finally add modified rubber powder and modified polyurethane compound to the mixture, mix and stir at 500r / min for 30min to obtain asphalt concrete.

3. An asphalt concrete according to claim 1 or 2, characterized in that: The chain extender is at least one of triethanolamine and diethanolamine.

4. An asphalt concrete according to claim 1 or 2, characterized in that: The coarse aggregate is crushed stone with a gradation of 10-20 mm.

5. An asphalt concrete according to claim 1 or 2, characterized in that: The fine aggregate is quartz particles with a gradation of 2-5 mm.

Citation Information

Patent Citations

  • Modified asphalt, asphalt modifier and preparation method thereof

    CN109135308A

  • Environment-friendly warm mix asphalt mixture and preparation method thereof

    CN111499272A